Minimally invasive aesthetic rehabilitation in composite resin: report of two clinical cases - Pedreira, Priscila Regis Matos; Damasceno, Janaina; Pierote, Josué; Dressano, Diogo; Marchi, Giselle Maria (Brazilian Dental Science, 2019)
Patient demand looking for the perfect smile has been steadily growing in the last few years. Thus, these two case reports discuss some ultra-conservatives approach to achieve good esthetic results. In the first case the clinical protocol of a restorative approach is described, the cosmetic remodeling of the teeth and in the second case, the replacement of extensive unsatisfactory composite restorations. The treatment planning was based on diagnostic waxing and the making of mock-up in both cases. Teeth bleaching were also performed before restoration. To conclude, these conservative relative therapies with composite resin restorations provide an ultra-minimally invasive protocol with excellent esthetic appearances and fuction, especially for young people. Keywords Dental esthetics; Composite resins; Smiling; Restoration.